Evolution of suicide mortality according to death mechanisms - 2001-2015 - Cyntia Meneses de Sá Sousa, Márcio Dênis Medeiros Mascarenhas, Patricia Viana Carvalhedo Lima, Juliane Danielly Santos Cunha, Malvina Thais Pacheco Rodrigues (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/reufpi.v9i0.9098